Psychosocial Assistance and Strengthening of Community-Based Islamic Education Services in Post-Flood Disaster Recovery in the Barus Area, Tapteng Regency - Nirwana Anas; Adi Hartono; Sapri Sapri (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT Flood disasters in the Barus area, Central Tapanuli Regency, caused psychosocial impacts and disrupted community-based Islamic education services, particularly local religious learning activities. This condition required assistance efforts aimed at restoring community psychological well-being while strengthening post-disaster Islamic educational services. This community service program aimed to provide psychosocial assistance and strengthen community-based Islamic education services for flood-affected communities in the Barus area, Central Tapanuli Regency. The program employed a participatory approach through field observation, community needs assessment, psychosocial assistance, educational and spiritual activities, and capacity strengthening for community-based Islamic education providers. The target participants included children, adolescents, Qur’anic teachers, and flood-affected residents. The activities contributed to increased learning motivation among children, improved emotional recovery within the community, and greater participation in community-based Islamic education activities. Strengthening educational services was also achieved through the provision of learning media, religious activities, and collaboration with local community leaders. Psychosocial assistance and the strengthening of community-based Islamic education services positively contributed to post-flood recovery efforts in the Barus area. The program supported the social, emotional, and spiritual resilience of the community while reinforcing the sustainability of Islamic education in disaster-affected areas. Keywords: Psychosocial Assistance, Islamic Education, Community Service, Post-Disaster Recovery, Flood Disaster.